2018
DOI: 10.1007/s00280-018-3704-7
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate polyglutamate levels and co-distributions in childhood acute lymphoblastic leukemia maintenance therapy

Abstract: Purpose Methotrexate polyglutamates (MTXpg) facilitate incorporation of thioguanine nucleotides into DNA (DNA-TG, the primary cytotoxic thiopurine metabolite and outcome determinant in MTX/6-mercaptopurine treatment of childhood ALL). We hypothesized that mapping erythrocyte levels of MTXpg with 1-6 glutamates and their associations with DNA-TG formation would facilitate future guidelines for maintenance therapy dosing. Methods and results Summed MTX with 1-6 glutamates resolved by LCMS [median (interquartile)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…ATRA is used in the treatment of acute promyelocytic leukemia and myelodysplastic syndrome. Two derivatives of ATRA (containing glutamic acid or its sodium salt), RAE and RAENa, have been synthesized, and they showed improved aqueous solubility and were more effective in mice bearing S-180 tumors and in childhood acute leukemia [14,15]. In the present study, we proposed glutamic acid as an adjuvant to increase MTX efficacy by promoting polyglutamate synthesis.…”
Section: Introductionmentioning
confidence: 89%
“…ATRA is used in the treatment of acute promyelocytic leukemia and myelodysplastic syndrome. Two derivatives of ATRA (containing glutamic acid or its sodium salt), RAE and RAENa, have been synthesized, and they showed improved aqueous solubility and were more effective in mice bearing S-180 tumors and in childhood acute leukemia [14,15]. In the present study, we proposed glutamic acid as an adjuvant to increase MTX efficacy by promoting polyglutamate synthesis.…”
Section: Introductionmentioning
confidence: 89%
“…To avoid the interference caused by recent drug intake, we excluded samples with excessive levels of MTX pg1 , defined as those in which the sum of MTX pg1-6 exceeded 2.7 3 MTX pg2-6 1 2.5, since we have shown that MTX short-chain measurements in samples above this threshold are excessively affected by recently administered MTX pg1 . 28 For each metabolite, we calculated time-weighted means (prefix wm ), weighting each measurement by the time between the previous and the adjacent measurements and allowing for a maximum weight of 7 days (ie, MTX pg measurements were regarded as representing the MTX pg level in the period from 3 days before until 3 days after blood sampling, unless other MTX pg measurements were available within that interval 24,28 ). Because each of the wm MTX pg fractions were distributed differently (supplemental Figure 1, available on the Blood Web site), we applied rank normalization to allow for uniform statistical modeling, despite different distributions.…”
Section: Quantification and Normalization Of Erythrocyte Mtx Polyglutamates And Leukocyte Dna-tgnmentioning
confidence: 99%
“…wm MTX pg2 and wm MTX pg4 among the 6 types of MTX polyglutamates were prioritized for further GWASs, based on our previous study on erythrocyte MTX polyglutamate profiling. 28 GWASs were then performed to evaluate the correlation between the 2 MTX polyglutamates (ie, wm MTX pg2 and wm MTX pg4 ) and genotypes at 1 495 495 SNPs in the discovery cohort (n 5 447) after quality control. A linear regression was applied with adjustment for sex, risk group, and genetic ancestry, as determined by principal components analyses.…”
Section: Mtx Polyglutamate Gwassmentioning
confidence: 99%
See 2 more Smart Citations